2013
DOI: 10.1158/0008-5472.sabcs13-s1-03
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S1-03: Primary results from BETH, a phase 3 controlled study of adjuvant chemotherapy and trastuzumab ± bevacizumab in patients with HER2-positive, node-positive or high risk node-negative breast cancer

Abstract: Background The humanized monoclonal antibody (mAb) trastuzumab (H) + chemotherapy (chemo) prolongs disease-free survival (DFS) in patients (pts) with HER2-positive breast cancer (BC) in the adjuvant setting. Vascular endothelial growth factor (VEGF-A), one central regulator of angiogenesis, is a downstream target of HER2. Tumors overexpressing HER2 also overexpress VEGF-A and exhibit increased angiogenic potential. Combining H with the anti-VEGF-A mAb bevacizumab (B) significantly decreased tumor volume vs B o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(51 citation statements)
references
References 0 publications
2
48
0
1
Order By: Relevance
“…The tolerability of XT was better in NSABP-B40 when these agents were administered before AC (21). Even with 70% of the patients having node-positive disease, the number of DFS events was much lower than expected, as has been observed in a number of adjuvant breast cancer trials (27)(28)(29)(30). This low event rate substantially decreased the power of the study to show superiority of the AC!XT arm.…”
Section: Discussionmentioning
confidence: 91%
“…The tolerability of XT was better in NSABP-B40 when these agents were administered before AC (21). Even with 70% of the patients having node-positive disease, the number of DFS events was much lower than expected, as has been observed in a number of adjuvant breast cancer trials (27)(28)(29)(30). This low event rate substantially decreased the power of the study to show superiority of the AC!XT arm.…”
Section: Discussionmentioning
confidence: 91%
“…Despite this premise, no improvement in DFS was observed in previous studies that explored the value of known antiangiogenic agents in the adjuvant treatment of breast cancer, 18,28,29 supporting the use of different treatment strategies such as CM maintenance.…”
mentioning
confidence: 94%
“…A noticeable dissociation was however observed in non-IBC with bevacizumab, which increased the pCR rate in the neoadjuvant setting (17,18) but had no impact on survival in the adjuvant setting of HER2-positive breast cancer (19,20). To study whether the increased pCR reported in the BEVERLY-2 study would ultimately translate into improved long-term outcomes for the included patients, we report here the results of a preplanned survival analysis after 3 years of follow-up, together with the prognostic value of circulating tumor cell (CTC) and circulating endothelial cell (CEC) count.…”
Section: Introductionmentioning
confidence: 99%